IDENTIFIKASI KEANEKARAGAMAN PAKU-PAKUAN (PTERIDOPHYTA) EPIFIT PADA HUTAN BEKAS TEBANGAN DI HUTAN PENELITIAN MALINAU – CIFOR SETURAN (Diversity Identification on The Pteridophytes Epiphyte at The Log Over Area At Malinau Forest Research – CIFOR Seturan) - Akas Pinaringan Sujalu (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
The aim from this research is to found out the various kinds of Pteridophytes epiphytes and its porophyte in the log over area to the broadness of 12 hectares in the Malinau Research Forest (MRF-CIFOR) Seturan – district of Long Loreh the regency of Malinau. In the Log Over Area being found 50 species with 2993 individual or 4,9 individual Pteridophytes epphytes at each Phorophyte. Species Lycopodium sp, Selliguea lima (v.A.v.R)Holt., and the family Polypodiaceae is the most ones Pteridophytes epiphytes at the crown, at the bark trees and at the bole trees. The porophyte are being found 610 trees consisting of 162 species in 101 genera of 44 families with 484 trees consisting each of them has got a diameter runs from 20-51 cm. The species of Shorea parvifolia Dyer, being the most one in wich 34 trees.Keywords: Pteridophytes epiphyte, porophyt, diversity